An Evaluation of the Occupational Stress Among Employees of Permodalan Nasional Berhad - Rukiah , A Samad (2012)
This is an evaluation study on occupational stress experienced among employees of Permodalan Nasional Berhad (PNB). It has four main objectives. The first objective is to determine the average level of occupational stress among the employees of PNB. The second objective is to identify the most common factors (stressors) that caused occupational stress among the employees of PNB The third objective is to determine whether there is a significant difference in occupational stress level experience by type A Behaviour Pattern (TABP) and type B Behaviour Pattern (TBBP). The fourth objective is to determine whether there are significant differences in term of the occupational stress levels experienced by subgroups of the demographic variable such as gender, marital status, age groups, position (designation), education level, length of service and division (work placement). The findings of this study showed that generally the employees of PNB were experiencing low occupational stress level.The most common factors that caused occupational stress among the employees of PNB were work overload,work condition and time management. In term of association, relationship with r=0.379 and reward system with r=0.308 seems to have stronger correlations with occupational stress level. There was no significant difference between the mean level of TABP and TBBP respondents of this study (p value > 0.05). Lastly, there were no significant differences in the occupational stress among the different subgroups of the demographic variables namely gender, marital status, age groups, position, education level and length of service (p value > 0.05). However,there is significant differences in the occupational stress among the different subgroups of the demographic variables namely division (p value < 0.05).